2019
DOI: 10.4103/apjon.apjon_32_19
|View full text |Cite
|
Sign up to set email alerts
|

Health Belief Model-based Intervention on Women's Knowledge and Perceived Beliefs about Warning Signs of Cancer

Abstract: Objective: Early detection of cancers essentially depends on knowledge of the warning signs. This study, therefore, aimed at investigating the effect of Health Belief Model (HBM)-based educational intervention on the knowledge and perceived beliefs of women about the warning signs of cancer. Methods: This experimental study with intervention ( n = 80) and control ( n = 80) groups was performed at four urban health ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
(26 reference statements)
4
11
0
Order By: Relevance
“…People in this practical model should initially feel threatened by the increased risk of BMI and chronic diseases (PSS) and subsequently perceive the risk severity and the significance of its various related-complications on physico-mental and socio-economic aspects (PSV). Individuals then would be able to observe optimistic signs received from their surroundings (CA) and to believe in the helpfulness and efficiency of prevention programs (PBF) with low obstacles to behavior change [ 17 , 18 ]. The assessment of HBM components before and after the intervention showed that there was no significant difference in CA and PBF-PBR.…”
Section: Discussionmentioning
confidence: 99%
“…People in this practical model should initially feel threatened by the increased risk of BMI and chronic diseases (PSS) and subsequently perceive the risk severity and the significance of its various related-complications on physico-mental and socio-economic aspects (PSV). Individuals then would be able to observe optimistic signs received from their surroundings (CA) and to believe in the helpfulness and efficiency of prevention programs (PBF) with low obstacles to behavior change [ 17 , 18 ]. The assessment of HBM components before and after the intervention showed that there was no significant difference in CA and PBF-PBR.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1 , the theoretical model presents the interrelationships of the constructs and panic buying behavior. The health belief model has been applied in the numerous community-based health interventions contexts [ 42 , 43 , 44 ] and its elements (i.e., perceived susceptibility, perceived severity, outcome expectancy, cues to action, and self-efficacy) explain the determinants of the perceived scarcity of products in the pandemic. This perceived scarcity subsequently leads to anticipated regret and panic buying behavior [ 52 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is one of the most used models for analyzing health-related behaviors. The health belief model has been applied in numerous community-based health intervention contexts, and its elements explain the determinants of health behavior during the COVID-19 pandemic [ 28 , 29 , 30 ]. In this study, factors of the HBM are comprised of cues to action, perceived benefits, perceived barriers, perceived severity, and perceived susceptibility.…”
Section: Conceptual Frameworkmentioning
confidence: 99%